Aortic valve endocarditis with Erysipelothrix rhusiopathiae: A rare zoonosis - Jenny Jónsdóttir Nielsen; Bjørn Blomberg; Shahin Gaïni; Steinar Lundemoen (MDPI AG, 2018)
Erysipelothrix rhusiopathiae has an economic impact in animal husbandry by causing infection in swine, sheep and poultry. E. rhusiopathiae is present in the surface mucoid slime on fish, although fishes do not seem to be affected. Humans can get infected, maost often through occupational exposure and may suffer typical erysipeloid infection on exposed skin such as on hands and fingers, or deeper skin infections, and sometimes sepsis and endocarditis, associated with high case-fatality rate. We describe a case of aortic valve endocarditis caused by E. rhusiopathiae in a 59-year-old man who enjoyed fishing in his spare time.